A peroxidase-derived ligand that induces Fusarium graminearum Ste2 receptor-dependent chemotropism - Sridhar, Pooja S.; Vasquez, Vinicio; Monteil-Rivera, Fanny; Allingham, John S.; Loewen, Michele C. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction The fungal G protein-coupled receptors Ste2 and Ste3 are vital in mediating directional hyphal growth of the agricultural pathogen Fusarium graminearum towards wheat plants. This chemotropism is induced by a catalytic product of peroxidases secreted by the wheat. Currently, the identity of this product, and the substrate it is generated from, are not known. Methods and results We provide evidence that a peroxidase substrate is derived from F. graminearum conidia and report a simple method to extract and purify the FgSte2-activating ligand for analyses by mass spectrometry. The mass spectra arising from t he ligand extract are characteristic of a 400 Da carbohydrate moiety. Consistent with this type of molecule, glycosidase treatment of F. graminearum conidia prior to peroxidase treatment significantly reduced the amount of ligand extracted. Interestingly, availability of the peroxidase substrate appears to depend on the presence of both FgSte2 and FgSte3, as knockout of one or the other reduces the chemotropism-inducing effect of the extracts. Conclusions While further characterization is necessary, identification of the F. graminearum-derived peroxidase substrate and the FgSte2-activating ligand will unearth deeper insights into the intricate mechanisms that underlie fungal pathogenesis in cereal crops, unveiling novel avenues for inhibitory interventions.